Training of trainers (Tot) by Soft Skills Department - UMP, CMLHS (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
24-26 February 2012. Sixty seven Universiti Malaysia Pahang students from both Gambang and Pekan campuses participated in the Training of Trainers (TOT) program organized by Soft Skills Department, Centre for Modern Languages and Human Science (CMLHS) over the weekend.